Osteonecrosis of the jaw in patients with clear cell renal cell carcinoma treated with targeted agents: a case series and large-scale pharmacovigilance analysis - Wang, Shuyun; Zhang, Rui; Wang, Song; Guo, Qian; Yin, Donghong; Song, Yan; She, Xianhua; Wang, Xuyan; Duan, Jinju (Frontiers in Pharmacology, 2024)
Objective: To optimize the use of tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) for cancer patients, we characterized and evaluated ONJ related to TKIs and ICIs by analyzing a public database and reviewing the relevant literature. TKIs and ICIs are limited to drugs that treat renal cancer recommended by the National Comprehensive Cancer Network Clinical Practice Guidelines in Oncology for Kidney Cancer.We described a case series of patients experiencing ONJ while on TKIs or ICIs. We also